Fixed Points of Multivalued Contractive Mappings in Partial Metric Spaces - Abdul Rahim Khan; Mujahid Abbas; Talat Nazir; Cristiana Ionescu (Abstract and Applied Analysis)
The aim of this paper is to present fixed point results of multivalued mappings in the framework of partial metric spaces. Some examples are presented to support the results proved herein. Our results generalize and extend various results in the existing literature. As an application of our main result, the existence and uniqueness of bounded solution of functional equations arising in dynamic programming are established.